The predictive value of neutrophil to lymphocyte ratio on 30-day outcomes in spontaneous intracerebral hemorrhage patients after surgical treatment: A retrospective analysis of 128 patients - Zhao, Yiqin; Xie, Yanfeng; Li, Shengjie; Hu, Mingliang (Frontiers in Neurology, 2022)
Objective: The purpose of this study was to explore the predictive value of neutrophil-to-lymphocyte ratio (NLR) on 30-day outcomes in spontaneous intracerebral hemorrhage (ICH) patients after surgical treatment. Methods: This retrospective study utilized data from ICH patients who underwent craniotomy or minimally invasive puncture and drainage (MIPD) between January 2015 and June 2021. The patients meeting the inclusion criteria were divided into two groups according to 30-day outcomes, namely favorable outcome group and poor outcome group. Sex, age, time from onset to admission, vital signs at admission, admission GCS score, diabetes mellitus, hypertension, hematoma volume, hematoma location, surgical approach, and NLR at different time point were all recorded and analyzed. Results: A total of 128 patients were finally enrolled in this study, including 32 and 96 patients in the favorable outcome group and poor outcome group, respectively. During the course of ICH, the changing trend of NLR was to increase first and then decrease and peaked within 48 hours after surgery. In the univariate analysis, systolic blood pressure, admission GCS score, hematoma volume, surgical approach and NLR within 48 hours after surgery were statistically significant. In the multivariable analysis, NLR within 48 hours after surgery (OR = 1.342, P<0.001) was an independent risk factor of the 30-day outcomes in ICH patients after surgical treatment. Receiver operating characteristic (ROC) analysis showed that the best predictive cut-off value for NLR within 48 hours after surgery was 12.35 (sensitivity 82.9%, specificity 81.8%, area under the curve 0.877) and 14.46 (sensitivity 55.1%, specificity 87.5%, area under the curve 0.731) for MIPD group and craniotomy group, respectively. Conclusions: In the process of ICH, the value of NLR was increasing first and then decreasing and peaked within 48 hours after surgery. NLR within 48 hours after surgery was an independent risk factor of the 30-day outcomes in ICH patients. The peak NLR greater than 12.35 or 14.46 in patients receiving MIPD or craniotomy reflected a poor prognosis, respectively.